Proof-of-principle for two-stage photodynamic therapy: hypoxia triggered release of singlet oxygen. Issue 94 (16th November 2020) - Ayan, Seylan; Gunaydin, Gurcan; Yesilgul-Mehmetcik, Nisa; Gedik, M. Emre; Seven, Ozlem; Akkaya, Engin U.
Abstract : Singlet oxygen, which is stored in the form of an endoperoxide, released under hypoxic conditions typically prevalent in most tumors. Abstract : We propose to overcome oxygen deficiency and light attenuation problems in photodynamic therapy (PDT), by separating photoexcitation and singlet oxygen delivery of the PDT process into two distinct operations to be carried out sequentially, at different locations. We now demonstrate the viability of this approach, using 2-pyridone derivative which yields a relatively stable endoperoxide. The initial storage endoperoxide obtained is transformed enzymatically into a more labile compound when placed in hypoxic cell cultures, and releases singlet oxygen significantly faster. The potential of this approach in advancing PDT beyond its current limits is exciting.